Echoes of Glory : Historic Military Sites across Texas - Alexander, Thomas E., 1931-; Utley, Dan K. (Book collections on Project MUSE., 2015)
In their previous book, Faded Glory: A Century of Forgotten Texas Military Sites, Then and Now, historians Thomas E. Alexander and Dan K. Utley chose to go beyond the familiar military sites of Texas-the Alamo or the San Jacinto battlefield, for example-to feature lesser known locations. The book successfully recovered these "forgotten" arenas for tourists and preservationists alike. Alexander and Utley now return with Echoes of Glory, and the result is another impressive catalogue that highlights the hidden gems of Texas history. Echoes of Glory explores two dozen rarely discussed but equally.